Oil and its markets - Roncaglia, Alessandro (PSL Quarterly Review, 2015)
Oil markets are extremely complex, being characterized by the interplay of economic, political, technological and ecological factors. The paper reviews the various critiques of the idea that oil prices are determined by supply and demand, with supply scarcity-constrained, and briefly recalls the model of ‘trilateral oligopoly’. This interpretative lens is applied with special reference to the golden period of the oil majors and the increasing importance of OPEC in the 1970s. However, the counter-crisis in the 1980s highlighted the limits of OPEC’s hold on the markets and the increasing role of financial markets in the determination of oil prices. Considering shale oil as an instance of technical change and its importance in the oil sector, the paper draws some basic conclusions. Among these is the author’s forecast that oil prices are likely to remain low in the medium run. JEL codes: L13, L71, Q40, Q41, Q43